Indigo naturalis for inflammatory bowel disease: evidence from animal studies and molecular mechanisms - Hu, Jie; Zhou, Mengen; Huang, Li; Guo, Xiutian; Mei, Pingping; Li, Peng; Wang, Yiting; Chen, Yan (Frontiers in Pharmacology, 2025)
BackgroundIndigo naturalis (IN) has been extensively used in prescriptions of traditional Chinese medicine to treat inflammatory bowel disease (IBD), particularly ulcerative colitis (UC). However, there is a lack of quantitative, evidence-based assessments from preclinical trials.AimsQuantitative statistical evidence regarding the efficacy of IN in animal models of IBD remains insufficient. This study performed a meta-analysis to evaluate the therapeutic effects of IN in experiments with IBD.MethodsRelevant animal studies were identified from PubMed, Web of Science, Embase, China National Knowledge Infrastructure, SinoMed, and Wanfang databases. Two researchers independently conducted literature screening and risk-of-bias assessments using the CAMARADES 10-point quality checklist. Meta-analysis was performed using Review Manager 5.4, focusing on the histopathological index as the primary outcome measure.ResultsOf the 15 eligible studies included, over half had low risks of bias in more than five items. Compared to controls, the histopathological index significantly improved after IN treatment (n = 151/137; SMD = −2.69 [-3.36, −2.02]; p < 0.00001). Subgroup analysis showed that a high dose of IN (>600 mg/kg; 4 studies, n = 31/22; SMD = −3.55 [-5.72, −1.39]; p < 0.001) was most effective in reducing the histopathological index. The IN group showed a significantly lower final disease activity index (DAI) score (n = 121/89; WMD = −1.69 [-2.18, −1.20]; p < 0.00001), greater percentage body weight recovery (n = 77/63; WMD = 9.99 [6.50, 13.49]; p < 0.00001), and longer colon lengths (n = 65/51; WMD = 0.95 [0.67, 1.24]; p < 0.00001) compared to controls. Additionally, IN treatment reduced IL-1β, IL-6, IL-8, and TNF-α expression while increasing IL-10 levels. These findings suggest that IN ameliorates inflammation by balancing innate and adaptive immunity, modulating the AhR/CYP1A1 signaling pathway, and altering gut microbiota structure.ConclusionIN demonstrated significant therapeutic efficacy in preclinical models of IBD, particularly at dosages exceeding 600 mg/kg. It protected colonic mucosal integrity and exerted beneficial effects through multiple molecular pathways.